Prevalência de infecção pelo Mycobacterium leprae na população da microrregião de Almenara, Minas Gerais - Angélica da Conceição Oliveira Coelho Fabri (2011)
The PGL-I surface antigen of Mycobacterium leprae, is responsible for activation of the immune response in individuals who come into contact with the bacillus. The serological anti PGL-I tests are used as a tool for identification of exposed individuals with subclinical infection or risk of disease and when associated to the clinic can help in the diagnosis of leprosy, besides they are useful for classifying the clinical form, since they have high sensitivity in multibacillary patients. The prevalence of seropositivity of the test may reflect approximately the rate of exposure / infection in a population. The purpose of this study was to analyze the prevalence of infection with M. leprae in the population of the microregion of Almenara, Minas Gerais. Hence, we opted for an epidemiological study, survey type, with a sample of 2726 individuals, randomly selected, from the stratification of census tracts, the second quartile, of average detection rate in the municipalities of Almenara, Felisburgo, Jacinto, Jequitinhonha, Monte Formoso, Ponto dos Volantes, Santa Maria do Salto e Santo Antônio do Jacinto. We carried out home visits to the enforcement of a structured questionnaire to obtain socio-demographic data, housing conditions, contact with patients of leprosy and of immunoprophylaxis, being also performed blood collection on filter paper for analysis of anti PGL-I. The immunoenzymatic method used for serological analysis was ELISA. The study was approved by the COEP-UFMG opinion nº ETIC 158/09 and meets the provisions of Resolution 196/96 of the National Health Council. The data entered into Epi Info v. 3.5.1 and analyzed using the Statistical Package for the Social Sciences 18 (SPSS) for Windows. We obtained an average seroprevalence of anti PGL-I of 1.03% and there was statistical association between age and anti PGL-I seropositivity, given that individuals aged between 15 and 29 years have approximately three times greater chance (OR = 3.23, CI = 1.05 to 9.90) of being seropositive compared to individuals of other age group. It follows that the municipalities at study showed rates of seropositivity of IgM anti PGL-I greater than the rate of detection of cases and their individuals are under high risk of getting the disease and, therefore it becomes important the clinical and serological follow-up to evaluate the progress or the clinical manifestation of the disease and if its needed to start chemotherapy treatment at a early stage, which would help breaking the transmission chain